Sustainability of on-farm income and employment through livestock production in Mathura district of Uttar Pradesh - DEOGHARE, P R (The Indian Journal of Animal Sciences, 2013)
A survey of the occupation of the farmers indicated that 68.51 % of the households had agriculture, of the households 10.20 % dairy, 20.40 % goat farming and 0.S9 % sheep farming as their main occupation. The number of family members and farm workers increased with the increase in size of land holdings. The overall average net income per household per year on livestock farming was 26.69 % whereas on crop farming, it was 73.13 %. Similarly, labour employment per household per year on an average under goat, sheep, buffalo and crop farming was 23.34, 1.96, 33. 17 and 41.53 % respectively.